2011
DOI: 10.1002/hep.24592
|View full text |Cite
|
Sign up to set email alerts
|

HAb18G/CD147 promotes cell motility by regulating annexin II-activated RhoA and Rac1 signaling pathways in hepatocellular carcinoma cells

Abstract: Tumor cells can move as individual cells in two interconvertible modes: mesenchymal mode and amoeboid mode. Cytoskeleton rearrangement plays an important role in the interconversion. Previously, we reported that HAb18G/CD147 and annexin II are interacting proteins involved in cytoskeleton rearrangement, yet the role of their interaction is unclear. In this study we found that the depletion of HAb18G/CD147 produced a rounded morphology, which is associated with amoeboid movement, whereas the depletion of annexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 45 publications
(61 reference statements)
7
100
0
Order By: Relevance
“…We further showed that RhoA and Rac1 were responsible for GPR116-induced cancer cell migration and morphology changes. Previous studies have shown that RhoA and Rac1 regulate the formation of an elongated cell morphology in macrophages (37) and regulate the motility of diverse tumor cells (38)(39)(40), which are consistent with our observations. Second, we found that GPR116 promoted breast cancer cell migration and invasion via Gaq signaling.…”
Section: Discussionsupporting
confidence: 93%
“…We further showed that RhoA and Rac1 were responsible for GPR116-induced cancer cell migration and morphology changes. Previous studies have shown that RhoA and Rac1 regulate the formation of an elongated cell morphology in macrophages (37) and regulate the motility of diverse tumor cells (38)(39)(40), which are consistent with our observations. Second, we found that GPR116 promoted breast cancer cell migration and invasion via Gaq signaling.…”
Section: Discussionsupporting
confidence: 93%
“…As a transmembrane glycoprotein, CD147 localizes to both the cell membrane and the endomembrane system in HCC cells. A recent study in our laboratory has proved that CD147 localizing to endomembrane system inhibits the RhoA/ ROCK signaling pathway and amoeboid movement via depression of annexin II phosphorylation (24). Although a previous study claimed that the ERK pathway was involved in FAK regulation by CD147 (23), further investigation is needed to study the responsible mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…We and others have demonstrated that CD147 influences migration and invasion via protease induction and cytoskeletal remodeling (10,27,66,67), although the exact signaling mechanisms regulating these processes are not understood. Here we have shown that up-regulation of CD147 in non-transformed breast epithelial cells leads to increased EGFR, Ras, and ERK activation.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%